Lease Stability in Agricultural Land: Legal Instruments in Poland and Selected European Countries (Universitas Muhammadiyah Yogyakarta, 2023)
This manuscript explores the legal instruments related to the stability of agricultural land lease in Poland and selected European countries. The study begins with a brief history and evaluation of land leasing in regions including Germany, France, Poland, and Switzerland. Despite its prevalence, the European Union lacks overarching regulations on this matter, leaving it to individual Member States. The research emphasizes lease duration, extension, and continuity, especially during events like the transfer of lease rights or the death of involved parties. A comparative analysis of legislation from countries like Poland, Germany, Italy, and France is presented. The paper also touches upon EU funds related to land leasing. In conclusion, various legal solutions across Europe are highlighted, underscoring the importance of stability for farm development and alignment with the Common Agricultural Policy.